Everyday Chinese an interactive storytelling toolkit in teaching Mandarin as a second language in context with Filipino-Chinese culture for children ages 3 to 5 in the Chinese school curriculum - Amoncio, Christi Nicole P.; Aguilar-Reyes, Mitzie Marie (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
Chinese education in the Philippines is not as effective compared to its state before the Filipinization process in 1975. This is due to a lot of factors. Students have become more localized, in which they are a mix of Filipinos and Filipino-Chinese. Most don't even speak Chinese at home anymore. In school, the teaching style is still traditional. This means students are implied to have a background on the language and Chinese school is where they practice their proficiency more by reading or writing. This comes out as memorizing without understanding. Moreover, the visuals used for teaching are from China or Taiwan, which makes the lesson unrelatable to the localized students. Teaching materials for 3 to 5 are not as interesting. Children at 3 to 5 are just beginning to make sense of the world around them through their senses. And their curiosity makes them restless. Rhymes and storytelling are used in teaching the language, with the intention for it to be fun and interesting. However, they are not done to hold the age group's interest. Despite 12 to 13 years of Chinese education, students are not proficient in the language as they should be because they are being drilled with Chinese terms and phrases instead of experiencing it. "Everyday Chinese: Play and Learn in Mandarin" is an interactive approach to teaching Mandarin as a second language. Moreover, it is localized to make the lessons familiar by showing the dualism of Filipino-Chinese culture. It is multisensory and play-based specifically catered to preschoolers, ages 3 to 5. This means the toolkit allows them to play using the magnetic storybook and the activities and songs included in it. Through this teaching strategy, learning the language becomes enjoyable and easily ingrained in the students because it is experienced.
Thesis (Bachelor of Fine arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 169-171.
Keywords: Storytelling in education -- Philippines; Schools, Chinese -- Philippines; Chinese language -- Acquisition; Storytelling -- Study and teaching